1997
DOI: 10.1128/jcm.35.4.1021-1023.1997
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Etest and agar dilution method for antimicrobial susceptibility testing of Flavobacterium isolates

Abstract: The Etest was evaluated as a possible alternative to the standard agar dilution method for susceptibility testing of nine antimicrobial agents against Flavobacterium species. In studies of 100 clinical isolates, the agreement between the MICs (؎1 log 2 dilution) obtained by the two methods was acceptable for cefotaxime, ceftazidime, amikacin, minocycline, ofloxacin, and ciprofloxacin (>90%). Conversely, the agreement between the results obtained for piperacillin was limited (84%). The overall agreement was 92.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Piperacillin, ofloxacin and ciprofloxacin are potential drugs of choice for the treatment of infections caused by chryseobacteria [6]. It has been shown that susceptibility disc diffusion testing is inaccurate for these organisms, since there is often a poor correlation between the disc diffusion results and the MIC values [5,7]. The reason for this remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Piperacillin, ofloxacin and ciprofloxacin are potential drugs of choice for the treatment of infections caused by chryseobacteria [6]. It has been shown that susceptibility disc diffusion testing is inaccurate for these organisms, since there is often a poor correlation between the disc diffusion results and the MIC values [5,7]. The reason for this remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We used the MIC breakpoints for ‘other non‐ Enterobacteriaceae ’[1]. The E test may be an alternative to the standard agar dilution method for testing susceptibility to ciprofloxacin and ceftazidime but not to piperacillin, since there may be discrepancies between the E test result and the standard agar dilution MIC for piperacillin [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…Minimal inhibitory concentrations (MICs) of vancomycin and imipenem were determined overnight with the E-test (AB Biodisk; Dalvagen) by use of Muller Hinton agar with a 0.5-McFarland bacterial suspension, which has been proven to be an alternative to the standard agar dilution method. 3 Interpretation of quantitative MIC results was in accordance with Clinical and Laboratory Standards Institute criteria. 4 The molecular epidemiological relatedness of the isolates was evaluated by arbitrarily primed polymerase chain reaction (PCR).…”
Section: Methodsmentioning
confidence: 99%
“…MICs of some synthetic compounds were determined for each antimicrobial agent by using agar dilution method 18 . The inhibition zone was measured in triplicates in different concentrations (0.5, 1.0, 2.0 ug/ml) and the mean values of MICs are tabulated in the following table.…”
Section: Determination Of Minimal Inhibitory Concentrations (Mics)mentioning
confidence: 99%